Konstruksi Kecerdasan Intelektual Peserta Didik Berdasarkan Perspektif Psikologi Islam: Kajian Fenomenologis terhadap Aktualisasi Potensi Akal - Nur Hasanah Harahapi; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
The construction of students’ intellectual intelligence has received attention in various previous studies; however, research that specifically discusses the actualization of the potential of reason from the perspective of Islamic psychology through a phenomenological approach remains limited. Most studies still define intellectual intelligence as a cognitive ability measured through academic achievement or Intelligence Quotient (IQ), and therefore have not provided a comprehensive understanding of the relationship between the function of reason, spirituality, and character formation. This study aims to explore and analyze the construction of students’ intellectual intelligence from the perspective of Islamic psychology through the experience of actualizing the potential of reason. This study used a qualitative approach with an interpretative phenomenological design, involving 15 student participants selected through purposive sampling. Data were collected through in-depth interviews, documentation, and reflective notes, and were then analyzed using phenomenological thematic analysis through the stages of coding, categorization, and theme interpretation. The findings show that intellectual intelligence from the perspective of Islamic psychology is constructed through five main dimensions, namely reason as a divine trust, the integration of rational thinking and spiritual awareness, self-reflection as a mechanism for intellectual strengthening, the actualization of intelligence through ethical behavior, and the influence of obstacles in optimizing the potential of reason. These findings contribute to the development of the concept of Islamic psychology by presenting a holistic model of intellectual intelligence and expanding understanding of the relationship among cognitive, spiritual, and moral dimensions in education. The conclusion of this study affirms the importance of integrating the function of reason and Islamic values in shaping students’ intelligence. The implications of this study include a theoretical contribution to the development of Islamic educational psychology and a practical reference for educational institutions in designing learning that integrates intellectual, spiritual, and character development. This study also opens opportunities for further research on the development of instruments for measuring intellectual intelligence based on Islamic psychology and their implementation at various levels of education.